The large-cap portfolio value investing and the hidden opportunity in big company stocks - Villalta, Thomas, 1970- (Bloomberg financial series., 2012)
"The practical guide to finding value and opportunity in large-cap stocks using investor behavior. Large-Cap is an abbreviation of the term "large market capitalization" and refers to the stock of publicly traded companies with market capitalization values of roughly more than $10 billion, like Walmart, Microsoft, and Ford. Because of their size, the conventional view is that these companies do not present investors with an ability to be opportunistic. The Large-Cap Portfolio + Website argues that, contrary to popular perceptions, significant opportunities exist in these stocks.Written with a fluency that both the savvy amateur and professional investor will understand, the book fills a void in the market by offering the practitioner a methodology to identify and approach the major assumptions that underlie valuation, with an emphasis on issues that are more relevant to the analysis of large-cap stocks. Full of useful information on how to reap the rewards of stocks that most investors avoid. Presents essential insights into understanding stock valuation. Includes an actionable chapter devoted to portfolio management. Packed with timely instruction, Large-Cap Portfolio gives readers invaluable insights and examples of how to build portfolios that will out-perform broad market benchmarks"--